Prevalence and Factors Associated with Depression Among Undergraduate Health Students in Usmanu Danfodiyo University, Sokoto, Nigeria - Ijapa A. Adamu; Harrison S. Akogwu; Kehinde J. Awosan; Oche O. Mansur; Musa H. Idris; Maryam H. Muhammad; Yahaya A. Lapai; Micheal Dasa; A. Shehu; A. Abubakar; Zaharadeen M. Dan-inna; Oluseyi S. Apanisile; et al. (Nigerian Frontline Medicine Journal)
BackgroundDepression is a common mental disorder, it is a significant contributor to the global burden of disease, and has been associated with suicidal tendencies even among students. This study aimed to assess the prevalence and factors associated with depression among undergraduate health students in Usmanu Danfodiyo University Sokoto, Nigeria.